An investigation on cloud computing adoption within information technology companies - Mohammadi, A.; Saeedikondori, A.; Nezakati, Hossein *; Sabermajidi, N.; Amer, H. J. (IGI Global, 2021)
Cloud computing is one of the most popular technology services, and its usage has increased significantly in recent years. This study aims to understand the factors that influence cloud computing adoption by Malaysian information technology (IT) companies. An in-depth review in the previous literature demonstrated a relationship between relative advantage, complexity, compatibility, top management support, firm size, technology readiness, competitive pressure, and trading partner pressure with cloud computing adoption in Malaysia. The study's findings displayed that relative advantage, compatibility, top management support, and competitive pressure significantly affect cloud computing adoption. The study contributes to applying new technological features of cloud computing adoption in the industry through a wide range of variables. The results also help companies foresee their IT investment when implementing cloud computing. The relative advantage is identified to have the highest impact on cloud computing adoption.